THE ROLE OF LOCAL GOVERNMENTS IN REGIONAL FINANCIAL MANAGEMENT FOR THE HANDLING OF THE CORONA VIRUS DISEASE 2019 (COVID-19) PANDEMIC - Fahrul Abrori (Fakultas Hukum Universitas Islam Malang, 2021)
The COVID-19 pandemic in Indonesia led the government to make policies as a stimulus to maintain the stability of society and the economy. The central government authorizes local governments to manage local finances to deal with covid-19 in their respective regions. This is because the local government better understands the needs of the region. The issue raised first, how is the relationship between the Central Government and Local Government in financial management for the handling of the covid-19 pandemic? Second, what is the role of local governments in regional financial management for the handling of the Corona Virus Disease 2019 covid-19 pandemic? Using normative juridical research methods with statutory approaches and concept approaches. The relationship between the Central Government and Local Government in Financial Management for the Handling of the covid-19 Pandemic is fiscal decentralization. The role of local governments in regional financial management for the handling of the Covid-19 pandemic is by refocusing activities, reallocating budgets, and using regional budgets.